Diabetes and consolidation of fractures (Ожирение и метаболизм, 2013)
One of the complications of diabetes in humans is inadequate bone formation resulting in osteopenia and slow consolidation of fractures. The basis of these pathological processes is a disruption of the regeneration of bone tissue in insulin deficiency and hyperglycemia, the mechanisms of which are highlighted in this mini-review. The published data indicate the need for careful monitoring of blood glucose levels and adequate replacement therapy for the prevention of skeletal complications of diabetes.